The way to the world market: the problem of raising the competitiveness of Russian businesses in the period of accession to the WTO (Путеводитель предпринимателя, 2020)
The article is devoted to some issues and peculiarities of the development of Russia as a WTO member countries. The basis of the article is devoted to the perspectives opening to Russia in the light of accession to this organization, it is impossible to evaluate them only as rainbow, there are the objective, visible to the naked eye, the reasons, which force us to change the outlook from positive to neutral or even negative.